A Little Goes a Long Way: Serial Transmission of Twitter Content Associated with Hurricane Irma and Implications for Crisis Communication - Lachlan, Kenneth A.; Xu, Zhan; Hutter, Emily E.; Adam, Rainear; Spence, Patric R. (Journal of Strategic Innovation and Sustainability, 2019)
Although numerous studies have attempted to analyze Twitter content related to crises and disasters, less is known about the prominence of serial transmission or the message attributes that drive retweeting. The current study examined 3.57 million tweets collected in the aftermath of Hurricane Irma. The findings suggest that informational tweets, those containing specific imperative language, and those containing graphic elements played a more prominent role in the conversation. Likelihood of serial transmission was not related to follower count or account verification. Implications for emergency management are discussed.